The Influence of Counseling and Media Leaflets on Increasing Dysmenorrhea Knowledge - Ni Nyoman Sri Artina Dewi; Dyah Woro Kartiko Kusumo Wardani; Dewi Novitasari Suhaid (EMBRIO: Jurnal Kebidanan, 2023)
Dysmenorrhea is a symptom that arises due to abnormalities in the pelvic cavity and interferes with daily activities, especially in school-age adolescents. It was reported that between 30% and 60% of young women who had dysmenorrhea did not go to school. Treatment of dysmenorrhea can be carried out pharmacologically or non-pharmacologically, depending on the aspect of knowledge. Counselling is known to be effective in increasing knowledge, and leaflets and printed media also facilitate the teaching and learning process. This study aims to determine the effect of counselling and leaflet media on increasing knowledge. The study used a non-equivalent control group design. The research sample was taken by simple random sampling using a questionnaire to assess knowledge about dysmenorrhea. The analysis used a paired t-test to determine the effect of counselling and leaflet media and an independent t-test to determine the most influential media. The results showed that there was an effect of increasing knowledge by providing material through counselling and leaflets (p <0.05). Leaflets are concluded to increase knowledge, compared to counselling.